Mouse models for muscular dystrophies: an overview - Maaike van Putten; Erin M. Lloyd; Jessica C. de Greef; Vered Raz; Raffaella Willmann; Miranda D. Grounds; Annemieke Aartsma-Rus; James Dowling; Maaike van Putten (The Company of Biologists, 2020)
Muscular dystrophies (MDs) encompass a wide variety of inherited disorders that are characterized by loss of muscle tissue associated with a progressive reduction in muscle function. With a cure lacking for MDs, preclinical developments of therapeutic approaches depend on well-characterized animal models that recapitulate the specific pathology in patients. The mouse is the most widely and extensively used model for MDs, and it has played a key role in our understanding of the molecular mechanisms underlying MD pathogenesis. This has enabled the development of therapeutic strategies. Owing to advancements in genetic engineering, a wide variety of mouse models are available for the majority of MDs. Here, we summarize the characteristics of the most commonly used mouse models for a subset of highly studied MDs, collated into a table. Together with references to key publications describing these models, this brief but detailed overview would be useful for those interested in, or working with, mouse models of MD.